Ethics in the journalistic enterprise - Restrepo, Javier Darío (2022)
In the midst of economic crisis, uncertainty has taken over journalistic enterprises and the drive to ensure profits, the interest on business may cast the ethical compass into oblivion. It is interesting, therefore, to reflect on the existing differences between an ethical enterprise and one which is not ethical and on the long and short term benefits. Being an ethical enterprise is arduous and demanding and requires commitment to product quality, point at which management and editorial interests converge. Here professional identity is a key element to define professional work.